(3fgGjI GdWdH aj TQM GdecJSHs - (3Ydj Hf eMeO Hf CjOeQ GdpLrdnOcj, YR GdOjf,J (B742 (3g` s ((3Shjai Hf CMeO GdYOhi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi CXgQ GdCjGJ GdHGgQI OGdI Ydi Cfg hGLH GdhLhO dPGJg hHYO Cf ef TQhW GdYde efaYg Cgdg s
(3BNQgG (B:s
(3hJLgO ai GdfajS hJYQa bOQ eG UGQ Edjc hJYJQa ddg HeG ChgHg Edjc Je GdSaQ GdKGfi s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B5 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B28s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1811s
Keywords: (3GdadSaI hGdefWbs